Expression of Endoglin in Bladder Carcinoma of Iraqi Patients - Rawaa Al-Chalabi (Journal of Global Pharma Technology, 2019)
Angiogenesis is an important process for tumor growth in almost all malignancies. Endoglin (CD105) is a membrane glycoprotein, part of the TGF beta receptor complex, which strongly expressed on the surfaces of cancerous cells. It has a vital role in angiogenesis, tumor growth, survival and metastasis of cancer cells to other locations in the body. Methods: This study designed to evaluate the role of endoglin immune expression in the development of bladder carcinoma by using monoclonal antibody, 137 biopsies of bladder carcinoma were collected from patients and 42 normal bladder tissues were collected from forensic autopsy. Results: 118 (86.13%) out of 137 tumors and 27 (64.26%) of normal tissues gave positivity with different scores while other biopsies expressed negative staining pattern. Score +3 showed the highest frequency among the tumor tissues while normal bladder tissues expressed score+1 as the highest one. Conclusion: endoglin is a marker of angiogenesis closely associated with malignant potential and bladder carcinoma development.Keywords: Endoglin, Angiogenesis, Urinary bladder Carcinoma (UBC)